New toxicity assays in the current drug development process – the zebrafish model bridging the gap between in vitro and in vivo researches - Pavić, Aleksandar (Archives of Pharmacy, 2022)
Developing a new drug through preclinical research, whether it is a new chemical entity or a biologic therapeutic, is a very complex and long process, which can take many years with a lot of uncertainty on its success. One of the fundamental challenges in this process is the discovery of effective molecules, understanding their mechanism of action inside a living organism, as well as potential toxic effects, which are traditionally tested in vitro and in vivo. In vitro or cell culture systems cannot recapitulate an entire organism. On the other hand, animal studies are not suitable for high-throughput screening and experience many difficulties. Therefore, introducing the zebrafish model (Danio rerio) into preclinical trials is a way to make drug development more efficient and financially viable, simplifying their path to clinical trials, while reducing failures in the later stages of this process. The zebrafish model has emerged as a promising biotechnological platform for this purpose, due to its high molecular-genetic, physiological and immunological similarity with mammals, including humans. Attractive characteristics such as small size and optical transparency of embryos and existence of various transgenic lines with fluorescently labelled cells, tissues or organs make them adequate experimental model for biomedical researches. Moreover, following 3Rs principles (replacement, reduction and refinement) for more ethical use of animals, the zebrafish is regarded as a valid alternative to mammalian animals for toxicity testing.